The COVID-19 pandemic and the changes in the birth rate in the city of Fortaleza (Research, Society and Development, 2024)
COVID-19, initially identified in China, is a coronavirus causing systemic damage with a high potential for morbidity and mortality. Given the pandemic's magnitude, societal changes are suggested, as observed in other historical catastrophes, particularly impacting health and birth rates. Thus, the objective of this study was to analyze birth rates in Fortaleza during the pandemic through socio-epidemiological profiles of women and pregnant individuals. It is an observational, retrospective, descriptive, quantitative study conducted with data from 2016 to 2021 obtained from Fortaleza's SINASC. Between 2016 and 2019, a significant reduction (p